Psicose, desinserção e laço social: um debate entre a psicanálise e o campo da saúde mental - Claudia Maria Generoso (2014)
The present research intends to question the issue of social insertion of psychotic patients when the latter is grounded only on a social-political perspective. This standpoint, based on the psychiatric reform, demanded an incursion to some of its major concepts, such as social exclusion, social inclusion, citizenship, and psychosocial rehabilitation, as well as a historical reappraisal of the notion of madness. The matter of habitation, one of the guidelines of psychiatric reform regarding social insertion, was the chosen pathway to analyze the singular forms through which each subject inscribes him/herself in the social order. Thusly, the clinical cases of Anita, Abraão, and Sr. Gabriel allowed a theoretical elaboration on habiting in a social-political versant, in opposition to the psychoanalytical versant of habiting language, establishing the debate between the fields of mental health and psychoanalysis. Finally, some considerations concerning the psychoanalytical approach were made, insofar as is enables the reflection on peculiar forms employed by the subjects regarding their inscription in the social bond from the savoir-faire with the jouissance or the real of the symptom.